The Influence of Digital Storytelling on Early Childhood Literacy Development - Hamid Mustafa; Farid Nasir Ahmed; Asad Wali Haider (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Digital storytelling is an innovative approach to improving early childhood literacy by combining traditional storytelling with digital media. This paper examines the impact of digital storytelling on children’s reading, writing, and comprehension skills. Through the analysis of various digital storytelling platforms, the study demonstrates how interactive stories can engage young learners, enhance language acquisition, and foster a love for reading at an early age.